Intravenous drug delivery in neonates: lessons learnt. Issue 6 (30th January 2014) - Sherwin, Catherine M T; Medlicott, Natalie J; Reith, David M; Broadbent, Roland S
Abstract : Intravenous drug administration presents a series of challenges that relate to the pathophysiology of the neonate and intravenous infusion systems in neonates. These challenges arise from slow intravenous flow rates, small drug volume, dead space volume and limitations on the flush volume in neonates. While there is a reasonable understanding of newborn pharmacokinetics, an appreciation of the substantial delay and variability in the rate of drug delivery from the intravenous line is often lacking. This can lead to difficulties in accurately determining the pharmacokinetic and pharmacodynamic relationship of drugs in the smallest patients. The physical variables that affect the passage of drugs through neonatal lines need to be further explored in order to improve our understanding of their impact on the delivery of drugs by this route in neonates. Through careful investigation, the underlying causes of delayed drug delivery may be identified and administration protocols can then be modified to ensure predictable, appropriate drug input kinetics.